National health insurance : now, later, never? - Daly, John Charles; Berenson, Robert A.; American Enterprise Institute for Public Policy Research (Washington, D.C. : American Enterprise Institute, 1980)
This public policy forum, part of a series presented by the American Enterprise Institute, is concerned with national health insurance.
Held on October 4, 1979 and sponsored by the American Enterprise Institute for Public Policy Research.
ne 04/05/2018
Loans
Keywords: Insurance; National health insurance